Computational implications of biophysical diversity and multiple timescales in neurons and synapses for circuit performance. (April 2016) - Gjorgjieva, Julijana; Drion, Guillaume; Marder, Eve
Abstract : Highlights: Biological neurons and synapses operate with many timescales. Many computational models of networks are timescale impoverished. Circuit operation can be understood from interacting nonlinear building blocks. Abstract : Despite advances in experimental and theoretical neuroscience, we are still trying to identify key biophysical details that are important for characterizing the operation of brain circuits. Biological mechanisms at the level of single neurons and synapses can be combined as 'building blocks' to generate circuit function. We focus on the importance of capturing multiple timescales when describing these intrinsic and synaptic components. Whether inherent in the ionic currents, the neuron's complex morphology, or the neurotransmitter composition of synapses, these multiple timescales prove crucial for capturing the variability and richness of circuit output and enhancing the information-carrying capacity observed across nervous systems.